Heavy Metal Distribution in Opportunistic Beach Nourishment: A Case Study in Greece. (28th November 2013) - Foteinis, Spyros; Kallithrakas-Kontos, Nikolaos G.; Synolakis, Costas
Abstract : The existence and distribution of persistent pollutants, such as heavy metals, in coastal sediment used for opportunistic beach nourishment, is a problem that has not received much attention. Here, we assessed the coastal sediments in one restoration project for the occurrence and distribution of heavy metals, by utilizing an Energy Dispersive X-Ray Fluorescence (EDXRF) system. Heavy metal point sources included (i) the effluents of small industries (tanneries), (ii) wastewater treatment plant effluents, and (iii) paint and oil scraps from substandard ship maintenance activities that take place on ports breakwaters. A few neighboring beaches were found to have similar heavy metal concentrations, with mean values of Cu, Zn, and Pb ranging from 80 to 130, 15 to 25, and 25 to 40 mg/kg, respectively. Existing legislation regarding dredging activities in Greece appears insufficient for sustainable and environmentally friendly nourishment. We conclude that before opportunistic beach restoration projects materialize with material borrowed from ports and harbors the quality of the dredged material needs to be assessed.